Trypan blue staining of filtering bleb in eyes with operated trabeculectomy - Dada, T; Bali, S J; Mohan, S; Bhartiya, S; Sobti, A; Panda, A (Nepalese Journal of Ophthalmology, 2012)
Objective: To report the use of trypan blue staining of the filtering bleb to assess its functional status in eyes undergoing phacoemulsification after trabeculectomy. Subjects and methods: This retrospective study was conducted at a tertiary eye care centre in North India and studied 33 eyes of 33 patients ( with previously operated trabeculectomy), who underwent phacoemulsification. Trypan blue dye (0.06%) was used to stain the anterior capsule. After completion of phacoemulsification, the staining of the trabeculectomy bleb was noted as diffuse, patchy, minimal or no staining. Results: Of the 33 eyes, 13 had diffuse staining (39.4%, mean IOP = 9.3 ± 2.2 mm Hg), 7 (21.2%, mean IOP= 15.5 ± 1.8 mm Hg) had patchy staining, 4 had minimal staining (12.1%, mean IOP= 17.5 ± 0.5mm Hg) and nine (27.3%, mean IOP= 19.3 ± 1.6 mm Hg) had no staining. These staining patterns were labeled as groups 1 - 4 respectively. Statistical analysis showed that the difference between the IOPs in Group 1 - 2 and between Group 2 - 3 was not significant statistically (p=0.682 and 0.665 respectively). However the differences between the IOPs between Groups 1 - 3, 1 - 4, 2 - 4, and 3 - 4 were found to be highly significant statistically (p<0.0005). Conclusions: Trypan blue dye can be used to test the amount of sub-conjunctival filtration in eyes undergoing phacoemulsification cataract surgery. DOI: http://dx.doi.org/10.3126/nepjoph.v4i2.6536 Nepal J Ophthalmol 2012; 4 (2): 224-229